2012
DOI: 10.1248/cpb.c112001
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of New Oxidation Systems Utilizing Oxometalate Catalysts

Abstract: This review describes our recent efforts in the development and application of new oxidation systems utilizing oxometalate catalysts. The novel use of heteropoly acid (HPA), an acidic oxometalate catalyst, in hypervalent iodine-mediated oxidations provided an effective strategy to generate cation radical species that enables a variety of direct C-H functionalizations of aromatic compounds. This strategy brought a facile biaryl synthesis and new spirodienone syntheses in aromatic oxidation chemistry. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 196 publications
(118 reference statements)
0
4
0
Order By: Relevance
“…In line with literature precedents and on the basis of the need for a blocking group and the reactivity observed with O -methylated substrate 21 , we propose that the oxidative dimerization may proceed through nucleophilic addition of 10 to an electrophilic radical cation (Figure ). We propose that the o -bromide 10 may be oxidized by VOF 3 /TFA/TFAA to form a phenoxyl radical cation ( 22 ), likely through a charge transfer complex . The o -bromine may potentially stabilize the radical cation through electronic effects.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with literature precedents and on the basis of the need for a blocking group and the reactivity observed with O -methylated substrate 21 , we propose that the oxidative dimerization may proceed through nucleophilic addition of 10 to an electrophilic radical cation (Figure ). We propose that the o -bromide 10 may be oxidized by VOF 3 /TFA/TFAA to form a phenoxyl radical cation ( 22 ), likely through a charge transfer complex . The o -bromine may potentially stabilize the radical cation through electronic effects.…”
Section: Resultsmentioning
confidence: 99%
“…We propose that the ortho -bromide 10 may be oxidized by VOF 3 /TFA/TFAA to form a phenoxyl radical cation 22 , likely through a charge transfer complex. 36 The ortho -bromine may potentially stabilize the radical cation through electronic effects. Moreover, calculations 5,37 support such stabilization effects by showing that the spin density can reside on the bromine atom of 22 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Organoiodine reagents, possessing reactivity similar to that of transition metals, are widely used in various organic reactions as selective oxidants and environmentally friendly reagents, including aminations, oxidations, halogenations, C–C bond-forming reactions, rearrangements, and transition-metal-catalyzed reactions. They are also used for the acetalization of carbonyl compounds. , In 2005, in a perspective of Moriarty group’s work in hypervalent iodine chemistry, it was reported that the alcoholysis of iodobenzene diacetate (PIDA: PhI­(OAc) 2 ) in MeOH can generate the active reagent (dimethoxyiodo)­benzene (PhI­(OMe) 2 ) . The concomitantly formed enolate anion 1′ subsequently adds to the PhI­(OMe) 2 to yield intermediate A , which results in intermediate B via the addition of a methoxide anion.…”
Section: Introductionmentioning
confidence: 99%